Unjust Enrichment - Comparative Legal Review - Pajtić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Unjust enrichment is very highly positioned as one of the sources of obligations in the Law on Obligations. Research of comparative legal literature (both doctrinal type and judgments of national courts) indicated significant differences in the attitude towards this institute both between the legal systems of continental law and within the corpus of countries in which the so-called common law system is dominant. In the paper, a detailed analysis of both domestic and comparative legal literature and court practice was carried out. During the research, special emphasis was placed on the positive legal solutions of other, primarily European legal systems. The analysis included both those legal systems (French, German) that have a decisive influence on the civil law codes of other continental law countries, as well as those that are of decisive importance in countries characterized by precedential law (Great Britain, United States of America). A review was also made of solutions from the Hungarian legal system, whose impact on our law is not nearly as far-reaching as the aforementioned legal orders, but due to the similarity of the genesis of civil law in our two countries in the last hundred years, they arouse interest. One of the basic differences between continental and Anglo-Saxon law is reflected in the fact that in the former the central question is whether there was a legal basis for the defendant to gain some benefit, while in precedent law the focus is on the question of whether the plaintiff has a basis to claim restitution. Consequently, in continental law systems, the court will, first of all, order the restitution of what the defendant unjustly acquired, while in "common law" systems the plaintiff has the obligation to first prove that he has a reliable basis for restitution. In addition to recognizing the differences between the two groups of systems, through analysis we also come to distinctions within the groups themselves. For example, unlike French law, German law, albeit with certain difficulties, resolves the problem of unjust enrichment due to the actions of a third party. According to our ZOO, when a part of one person's property has been transferred in any way to the property of another person, and that transfer has no basis in a legal transaction or in the law, the acquirer is obliged to return it, and when this is not possible - to compensate the value of the benefits achieved. Obligation to return, i.e. compensation of value also occurs when something is received with regard to a basis that was not realized or that later fell away. The obligation to return is not subject to those goods that were given in the name of fulfilling some natural obligation or some moral or social duty, amounts that were paid even though the payer knew that he was not obliged to make the payment, as well as funds that, without a legal basis, were paid in the name of compensation for damages due to bodily injury, health impairment or death, if the payment was made to a bona fide recipient. The review of domestic judicial practice shed light on a wide range of situations in which legally unjustified enrichment can occur, i.e. acquisition without grounds. Although we are talking about an institution that has long been present as a source of obligations in the Law on Obligations, certain judgments, which are contra legem, show that in connection with this institution there are, still, numerous doubts.
Keywords: unjust enrichment, quasi-contract, condition suit